The Method Of The Influence Of Leading Inquiry Learning On Student Learning Outcomes In Ecosystem Main Materials - Khoirudin, M.; Novitasari, Cici (IJIS Edu : Indonesian Journal of Integrated Science Education, 2019)
The inquiry learning method in its development has a role in education in schools. In its implementation, the learning method for incuri plays a role for both teachers and students in the learning process, because the incuri method focuses on the activity of students in the learning process, while the teacher as a facilitator and mitivator when the learning process begins.The method used was Quasi Experiment with the Nonequeivalent Contol Group Design. This research was conducted at MT Agung Bandar Agung, East Lampung. In this study consisted of two groups namely the experimental and control groups. Learning outcomes instruments are in the form of a multiple choice form test that has been tested for validity, reliability and distinguishing features and the degree of difficulty. Data analysis using t-test on significance level of 0.05 can be seen from t table> t table.The results of the study revealed that, the learning outcomes of students after using the guided inquiry method was "significant" with an average final test of 84.83. While the learning process without using the guided inquiry method has a "less significant" qualification of 59.16. The t-test for the value of the final test obtained tcount> t table is 10.067> 1.658 at a significant level of 5% or 0.05. This is according to the t-test criteria which means that Ho is rejected and H1 is accepted. From this study it can be concluded that the learning outcomes of students who use guided inquiry methods have a positive effect on learning outcomes in the subject matter of the ecosystem.